CELEBRITY ENDORSEMENT AND BRAND IMAGE: EFFECTIVE STRATEGIES TO INCREASE PURCHASE INTENTION OF FASHION PRODUCTS ON E-COMMERCE PLATFORMS - Jubaidi, Muhammad Afif; Wolor, Christian Wiradendi; Fawaiq, Muhammad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
Currently, fashion products are able to become a dream in e-commerce purchases, so that the fashion product business is currently very competitive, especially in Indonesia. The purpose of this study is to investigate how celebrity endorsement and brand image influence purchase intention of fashion brands in e-commerce. The research method used in this study is a quantitative method, and the data collected are primary data through surveys, with the sampling technique chosen being purposive sampling, this study involved 200 respondents. The data that has been collected is then processed using AMOS software in addition to Structural Equation Modeling (SEM) using CFA and hypothesis testing. The results of the study, celebrity endorsement significantly influences purchase intention, brand image significantly influences purchase intention, and celebrity endorsement significantly influences brand image.